TINGKAT PENDAPATAN NELAYAN PENANGKAP IKAN KURISI SELAMA PANDEMI COVID-19 DI KAMPUNG PARA I KECAMATAN TATOARENG KABUPATEN KEPULAUAN SANGIHE - Costantein Imanuel Sarapil; Fitria Fresty Lungari; Eunike Irene Kumaseh; Ishak Bawias; Ganjar Ndaru Ikhtiagung; Erlin Puspaputri; Stefanus Kawowode (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2021)
This study aims to analyze at the income level of fishermen in Para I Village during the Covid-19 pandemic, and look at the marketing flow and marketing margins of Threadfin bream in Para I village. This research can be input to the Government in improving the welfare of fishermen amid Covid-19 pandemic. This research was conducted in Para I Village, Tatoareng District, Sangihe Islands Regency in March – May 2021. The methods used in this study were qualitative and quantitative ones. Data collection was carried out through direct observation and interviews with local fishermen, while maintaining health protocols. The income of threadfin bream fisherman per week in Para I Village ranges from IDR 500,000 - IDR 3,000,000 depending on weather condition. The marketing of threadfin bream and other demersal fish belongs to an efficient one. During the pandemic, fishermen's income decreased slightly because they could not bring their catch to be sold to Tahuna city or Dagho Fishing Port. However, there are also traders who come directly to buy fish on Para Island. Income decreased to IDR 500,000 per week during the pandemic. However, this condition only lasted for 2-3 months, but then their income returned to the normal. The strategy taken by fishermen to deal with the income decline during the pandemic is to process their catch into salted fish that can be sold or stored as food reserves for their households. The government can help organize Financial Management Training and education about business opportunities in the fisheries sector.